1997
DOI: 10.1210/endo.138.4.5065
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Hypothalamo-Pituitary-Adrenal Axis by the Growth Hormone (GH) Secretagogue, GH-Releasing Peptide-6, in Rats

Abstract: GH-releasing hexapeptide (GHRP-6) is a synthetic secretagogue that stimulates the release of GH by acting at both hypothalamic and pituitary sites. GHRPs also consistently elicit small, but significant, increases in plasma concentrations of ACTH and adrenal steroids. As these secretagogues do not release ACTH directly, they probably interact with the hypothalamic peptidergic systems controlling ACTH release, such as CRH and arginine vasopressin (AVP). We have now examined the activation of the hypothalamo-pitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 46 publications
3
42
1
Order By: Relevance
“…Among the effects of GHS-R ligands unrelated to GH release, moderate but consistent elevation of serum adrenocorticotropin (ACTH) and glucocorticoid levels have been reported for a variety of GHSs in different species (2,5,6,8,9,23). In good agreement, it was shown recently that ghrelin is able to elicit ACTH and cortisol responses in humans (18,20), as well as ACTH and corticosterone release in rats and mice respectively (19,24).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Among the effects of GHS-R ligands unrelated to GH release, moderate but consistent elevation of serum adrenocorticotropin (ACTH) and glucocorticoid levels have been reported for a variety of GHSs in different species (2,5,6,8,9,23). In good agreement, it was shown recently that ghrelin is able to elicit ACTH and cortisol responses in humans (18,20), as well as ACTH and corticosterone release in rats and mice respectively (19,24).…”
Section: Introductionmentioning
confidence: 72%
“…In addition, GHSs are able to elicit a number of biological responses in different endocrine and non-endocrine systems. These include modulation of food intake (3,4), stimulation of prolactin secretion (2, 5 -7), activation of the corticotropic axis (2,5,6,8,9), as well as a variety of cardiovascular effects (10,11). Recently, an unexpected widespread pattern of GHS-binding sites in a variety of peripheral tissues has been demonstrated in humans (12), thus not only providing the basis for their currently known effects, but also strongly suggesting additional, as yet undefined, biological actions of these synthetic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…However, Thomas et al (1997) have shown that GHRP-6 mediated the release of ACTH and cortisol in conscious rats. The mechanism by which ghrelin and synthetic GHSs stimulate the pituitary-adrenocortical axis is still unknown, but seems to be mediated via the hypothalamus as it is lost after cutting the pituitary stalk (Loche et al, 1995).…”
Section: Ghrp-6mentioning
confidence: 97%
“…The mechanism by which ghrelin and synthetic GHSs stimulate the pituitary-adrenocortical axis is still unknown, but seems to be mediated via the hypothalamus as it is lost after cutting the pituitary stalk (Loche et al, 1995). They may interact with hypothalamic peptides (e.g., corticotrophin-releasing hormone, arginine vasopressin, and neuropeptide Y) controlling ACTH release (Broglio et al, 2003;Dickson and Luckman, 1997;Korbonits et al, 1999;Thomas et al, 1997), most probably primarily via arginine vasopressin (Korbonits et al, 1999). In swine, some recently developed selective GHSs, such as ipamorelin, induced massive GH secretion without any elevation in ACTH, cortisol, or PRL release (Raun et al, 1998), whereas GHRP-6 and GHRP-2 administration in this species caused a strong activation of the pituitary-adrenocortical axis.…”
Section: Ghrp-6mentioning
confidence: 99%
See 1 more Smart Citation